Palm Pre pre-mature. - Aguilera, Ray.
Palm's bid to produce an iPhone killer is gutsy, but without significant work, the Pre won't dethrone Apple's smartphone any time soon.
Keywords: iPhone (Smartphone); Palm Pre (Smartphone)